(untitled) (Veterinary Science, 2020)
For effective sheep production, males and females in good nutritional status, healthy and functional, are needed. The nutritional status can be known through the body condition score, whose evaluation allows corrections in management and increase the productive and reproductive efficiency of sheep according to their physiological status. The objective of this study was to evaluate the body conditioning sheep in relation to their physiological state trough semi-technical exploration, and on this basis make a diagnosis of reliable productive and reproductive situation. The study was carried out in the northern part of La Pampa province, in 8 mixed farms in spring-summer. A disparity of corporal sate was observed in sheep’s with the same physiological state in a sheep flock which means unfit animals. There is a tendency of the productive cycle to lean towards inefficiency that requires management interventions as to synchronize its stages with an optimal animal’s state and achieve maximum development.